Taxonomy, palynology and distribution notes of seven species of Passiflora L. (Passifloraceae s.s.) newly recorded from Brazil - Ana Carolina Mezzonato-Pires; Michaele Alvim Milward-de-Azevedo; Cláudia Barbieri Ferreira Mendonça; Vania Gonçalves-Esteves (PhytoKeys, 2018)
Passiflora subgenus Astrophea is one of the five recognised subgenera of Passiflora. Brazil presents ca. 26 species of this subgenus with the majority distributed in the Amazon Basin. During the ongoing taxonomic revision of the Brazilian species of subg. Astrophea, seven species previously unknown for the country were recorded: Passiflora amoena, P. fuchsiiflora, P. jussieui, P. ovata, P. plumosa, P. quelchii, and P. tessmannii. The new records expand the species distribution ranges, especially for P. plumosa, which was exclusively known from its type locality and P. quelchii, which was known only for southeastern Guyana. The authors provide taxonomic and palynological descriptions, distribution maps and illustrations for these species, in the hope that the knowledge and understanding of Brazilian Passifloraceae s.s. will be improved.